Vd-pq; a velocity-dependent viscous damping model for wave-structure interaction analysis - Michailides, Constantine (My University, 2021)
For the analysis and design of coastal and offshore structures, viscous loads represent one of the most influential parameters that dominate their response. Very commonly, the potential flow theory is used for identifying the excitation wave loads, while the viscous damping loads are taken into consideration as distributed drag type loads and/or as linear and quadratic damping loads approximated with the use of motion decay curves of the structure in specific degrees of freedom. In the present paper, is developed and proposed a numerical analysis method for addressing wave-structure interaction effects through a velocity-dependent viscous damping model. Results derived by a computational fluid dynamics model are coupled with a model that uses the boundary element method for the estimation of the viscous damping loads iteratively in every time-step of the analysis. The computational fluid dynamics model solves the Navier–Stokes equations considering incompressible flow, while the second model solves the modified Cummins Equation of motion of the structure in the time domain. Details about the development of the coupling method and the velocity-dependent viscous damping (VD-PQ) are presented. The coupling between the different models is realized through a dynamic-link library. The proposed coupling method is applied for the case of a wave energy converter. Results derived with the use of the developed numerical analysis method are compared against experimental data and relevant numerical analysis predictions. The importance of considering the instantaneous velocity of the structure in estimating the viscous damping loads is demonstrated. The proposed numerical analysis method for estimating the viscous damping loads provides good accuracy compared to experimental data and, at the same time, low computational cost.
Keywords: Wave-structure interaction; Viscous damping loads; Hydrodynamic analysis; VD-PQ method; Linear and quadratic damping; Wave energy converters